2013
DOI: 10.1007/s40436-013-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral teleoperation with reducing wave-based reflections

Abstract: This paper presents a wave-based bilateral teleoperation structure to reduce the wave reflection and enhance the force and speed tracking performance through adjusting the relative parameters. A time domain passive approach is also applied to deal with the passivity of whole system even with non passive environment. The efficiency of the proposed method is confirmed by some experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…With the modified 4-CH architecture, wave reflections were mitigated, the signal transmitted was improved while satisfying passivity argument. Zeng et al in [42] suggested a wave-based bilateral teleoperation approach using time domain passivity control to mitigate wave reflection and improve tracking performance. However, the two major categories for attenuating wave reflections are impedance matching and filtering techniques.…”
Section: Introductionmentioning
confidence: 99%
“…With the modified 4-CH architecture, wave reflections were mitigated, the signal transmitted was improved while satisfying passivity argument. Zeng et al in [42] suggested a wave-based bilateral teleoperation approach using time domain passivity control to mitigate wave reflection and improve tracking performance. However, the two major categories for attenuating wave reflections are impedance matching and filtering techniques.…”
Section: Introductionmentioning
confidence: 99%